Effect of Cleaning and Storing on Hatching Time and Hatching Weight of Mojosari Alabio (MA) Crossbred Duck Eggs - Ramon, Erpan; Efendi, Zul; Nurhaita, Nurhaita; Hidayat, Taufik; Permadi, Selma Noor; Firison, Jhon; Ishak, Andi (Faculty of Agriculture, 2024)
ABSTRACT. The hatchability of duck eggs is influenced by handling before the eggs are placed in the incubator. The research was conducted in Bengkulu City from September to October 2021 to determine the effect of cleaning and storage before incubation of MA duck eggs from crossing Mojosari males and Alabio females on hatching time and hatching weight. The research was conducted using a completely randomized factorial design (4x6). The first factor is cleaning with three treatments, namely control or no cleaning (L0); cleaning using two ml/l disinfectant (L1), cleaning using warm water (L2), and cleaning with distilled water (L3). The second factor is the storage time, namely P0= 0 days, P1= 1 day, P2= 2 days, P3= 3 days, P4= 4 days, and P5= 5 days. There were eight repetitions of each treatment. According to the study, there was an average of 96% egg fertility and 87.45% hatchability. There was no interaction effect (P0.05) between cleaning and storage on egg hatching time. Cleaning with disinfectant or distilled water shortened the incubation time. Cleaning with distilled water without storage resulted in the highest hatching weight of duck eggs (L3P0) but was not significantly different from treatments L0P1, L1P0, L1P3, L1P5, L2P0, L3P0, and L3P3. Hatching weight is influenced by the interaction effect between egg cleaning and storage.Pengaruh pembersihan dan penyimpanan terhadap waktu penetasan dan berat tetas telur itik persilangan Mojosari Alabio (MA)ABSTRAK. Daya tetas telur itik dipengaruhi oleh penanganan sebelum telur dimasukkan ke inkubator. Penelitian dilakukan di Kota Bengkulu pada Bulan September sampai Bulan Oktober 2021 dengan tujuan untuk mengetahui pengaruh pembersihan dan penyimpanan sebelum inkubasi telur itik MA hasil persilangan jantan Mojosari dan betina Alabio terhadap waktu tetas dan bobot tetas. Penelitian dilakukan dengan menggunakan rancangan acak lengkap faktorial (4x6). Faktor pertama pembersihan dengan tiga perlakuan yaitu kontrol atau tidak ada pembersihan (L0); pembersihan menggunakan disinfektan 2 ml/l (L1), pembersihan menggunakan air hangat (L2), dan pembersihan dengan akuades (L3). Faktor kedua adalah lama penyimpanan yaitu P0= 0 hari, P1= 1 hari, P2= 2 hari, P3= 3 hari, P4= 4 hari, dan P5= 5 hari. Setiap perlakuan diulang sebanyak delapan kali. Hasil penelitian menunjukkan bahwa fertilitas telur rata-rata 96% dengan daya tetas 87,45%. Tidak terdapat pengaruh interaksi (P0,05) antara pembersihan dan penyimpanan terhadap waktu penetasan telur, namun pembersihan dengan disinfektan atau dengan aquades mempersingkat waktu inkubasi. Pembersihan dengan akuades tanpa penyimpanan menghasilkan bobot tetas telur itik tertinggi (L3P0) namun tidak berbeda nyata dengan perlakuan L0P1, L1P0, L1P3, L1P5, L2P0, L3P0, dan L3P3. Bobot tetas dipengaruhi oleh efek interaksi antara pembersihan dan penyimpanan telur.